PENGARUH SKEPTISME PROFESIONAL, INDEPENDENSI, DAN TEKANAN WAKTU TERHADAP TANGGUNG JAWAB AUDITOR DALAM MENDETEKSI KECURANGAN - Regita Ardilassinta Putri, (2020)
This study aims to determine the effect of Professional Skeptics, Independence and Time Pressure towards the auditor's responsibility in detecting frauds. Objects of this study are auditors working in South Jakarta. Sample used on this study are 40 respondents from 8 Public Accounting Firms in South Jakarta. Sampling technique used in this study is Purposive Sampling with predetermined criteria. The data used in this study are Primary Data from questionnaires which researcher spreads to auditors working in South Jakarta. Hypothesis testing in this research is multiple linear regression analysis by using SPSS program 2.0 with 0,05 or 5% significance level. Partial result of this study shows that Professional Skeptics positively affecting the auditor's responsibility in detecting frauds, Independence positively affecting the auditor's responsibility in detecting frauds, and Time pressure does not affect the auditor's responsibility in detecting frauds.